Relationship Between Adolescents’ Leisure Boredom and Substance Use in Turkey - Tennur Yerlisu Lapa; Ezgi Ertüzün (Türk Spor ve Egzersiz Dergisi)
This study aimed to determine the relationship between adolescents’ leisure boredom, substance use, and participation in recreational sports in a high-risk substance use region of Turkey. To determine high-school adolescents’ socio-demographic characteristics, data collection relied on an adolescent self-report data form and ‘substance’ and ‘boredom’ subscales of the Adolescent Risk-Taking Scale and Leisure Boredom Scale, respectively (n = 235, all males, Mage = 15.75 years, SD = 1.19). While there was a positive correlation (r = 0.43) between leisure boredom and substance use, a small significant negative relationship was observed between leisure boredom and participation in recreational sports (r = - 0.27) and between substance use and participation in recreational sports (r = -0.16). However, as research has shown that recreational sport activities may play an effective role in preventing leisure boredom, the results of the present study suggest that sports may play role in preventing substance use as well.